Novel Mutation at Cys225 in GNAO1‐Associated Developmental and Epileptic Encephalopathies: Clinical, Molecular, and Pharmacological Profiling of Case Studies - Yonika A. Larasati; Gonzalo P. Solis; Alexey Koval; Marie‐Céline François‐Heude; Julie Piarroux; Agathe Roubertie; Ruihan Yang; Ying Zhang; Dezhi Cao; Christian M. Korff; Vladimir L. Katanaev (MedComm)
ABSTRACT GNAO1‐associated disorders have a large spectrum of neurological symptoms, from early‐onset developmental and epileptic encephalopathies (DEE) to late‐onset movement disorders. First reported in 2013 and now identified in around 400 cases worldwide, this disease is caused by dominant, mostly de novo missense mutations in GNAO1, the gene encoding the major neuronal G protein Gαo. Being the immediate transducer of a number of neuronal G protein‐coupled receptors, Gαo plays crucial functions in brain development and physiology. Here, we discover a novel mutation site in GNAO1, Cys225 mutated to Tyr or Arg in pediatric individuals from France and China (p.(Cys225Tyr) and p.(Cys225Arg), respectively), leading to severe early‐onset DEE. Molecular investigations characterize the novel pathogenic variants as deficient in the interactions with guanine nucleotides and physiological cellular partners of Gαo, with reduced stability and plasma membrane localization and a strong neomorphic interaction with the chaperone Ric8A. Salts of zinc, emerging as a promising targeted therapy for GNAO1‐associated disorders, impose a previously unseen effect on the mutant Gαo, accelerating the loss of its ability to interact with guanine nucleotides. Our study, combining clinical, cellular, molecular, and modeling approaches, describes deep insights into molecular etiology and treatment perspectives of the novel form of GNAO1‐associated disorders.